The Inaugural Australian Centre for Hepatitis Virology Public Panel Discussion on Viral Hepatitis Research—Lessons in Scientific Community Outreach - Thomas Tu; Chaturaka Rodrigo; Simone I Strasser; D Scott Bowden; Jennifer H MacLachlan; Heidi E Drummer (Viruses, 2021)
Viral hepatitis remains one of the most significant health issues globally, directly responsible for over 1 million deaths each year and affecting almost 300 million people around the world. Scientific research in recent decades has brought about improvements in the lives of people living with chronic viral hepatitis. On the 29 July 2021, the Australian Centre for Hepatitis Virology (ACHV) for the first time held a public educational forum for the general public. The main aim of this event was to inform the affected community about the importance of scientific research and give an overview of upcoming developments in the field. Here, we provide a detailed report of the panel discussion (including its organisation, execution, and lessons learned to incorporate into future events) and provide strategies that can be used by other scientific societies to hold similar events in their own communities.